2019
DOI: 10.3904/kjim.2017.203
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of urticaria including physical urticaria and angioedema in Korea

Abstract: The prevalence of urticaria has increased annually in Korea. Cholinergic urticaria showed unique distribution in its age and gender, and angioedema showed remarkable increases in annual prevalence, although the prevalence estimation is still exploratory and diagnosis of urticaria based on ICD-10 codes need to be validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 18 publications
(27 reference statements)
4
48
3
1
Order By: Relevance
“…Our group previously reported the prevalence of CholU among chronic urticaria patients of 0.9% and 0.5% in the years 2007 and 2011, respectively [20,21]. The reported prevalence of CholU among general population in countries located in the tropical zones ranged from 0.023 to 11.2% [6][7][8]. Most studies including our study have shown the male predominance [6].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our group previously reported the prevalence of CholU among chronic urticaria patients of 0.9% and 0.5% in the years 2007 and 2011, respectively [20,21]. The reported prevalence of CholU among general population in countries located in the tropical zones ranged from 0.023 to 11.2% [6][7][8]. Most studies including our study have shown the male predominance [6].…”
Section: Discussionsupporting
confidence: 50%
“…In severe patients, CholU may be related to exercise-induced anaphylaxis, a severe wheal-flare reaction with systemic involvement including difficult breathing, wheezing, or abdominal pain [5]. The reported prevalence of CholU in a general population varies from 0.023% to 11.2% in temperate zone countries [6][7][8]. CholU mostly affects patients with age onset in their second to third decade [9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cholinergic urticaria in the general population is also debated, but one study has suggested that 11% of young adults can have mild disease [20]. Conversely, a recent Korean epidemiological study has estimated that the prevalence of dermatographism and cholinergic urticaria in the general population is 0.12% and 0.025% respectively [21]. As cholinergic urticaria is produced by elevation/reduction of core body temperature, it is also reasonable to see an association between cholinergic and cold-induced urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for female predominance could be that 35-40% of chronic urticaria have an autoimmune origin [ 4 ]. In contrast, cholinergic urticaria had been slightly more common in males compared to females in another study [ 21 ].…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, 70% of children had urticarial symptoms for at least one-year duration. However, a study from South Korea reported that most children had symptoms for less than one-year duration [ 21 ]. This could be due to the fact that most children in the current study were initially managed by general practitioners before they were referred to paediatricians.…”
Section: Discussionmentioning
confidence: 99%